The Smart Nutrition and Conditioning for Kids (SNACK) Program: An Approach to Increasing Nutrition Knowledge of Second-Grade Students. Issue 5 (September 2018) - Jakubowski, Tami L.; Perron, Tracy; Farrell, Anne; Kenner, Carole; Hullings, Christy
Abstract: Background: The Smart Nutrition and Conditioning for Kids (SNACK) program was developed in response to the 2010 Childhood Obesity Study (Rutgers Center for State Health Policy, 2010 ) recognizing a 49% childhood obesity rate in Trenton New Jersey. Lifestyle influences contributing to childhood obesity and Type 2 diabetes mellitus include poor food choices, inadequate access to healthy foods, decrease in physical activity, and insufficient access to safe play environments. Methods: Second-grade students were selected by teachers to be in the SNACK intervention group or a control group based on their classroom assignment. The SNACK program integrated nutrition lessons to students in an urban and urban rim elementary school during regularly scheduled physical education class. Nutrition lesson plans were developed to educate the children on healthy eating in a fun, interactive manner. The SNACK intervention was performed twice a week for 8 weeks. Pre- and poststudy CATCH (CATCH [Coordinated Approach to Child Health] Global Foundation, 2017) Nutritional Knowledge surveys were completed by all of the participating children. Results: Students who were offered the nutrition-based lessons (SNACK intervention group) performed better on their Healthy Choices survey ( p < 0.05), but not the Nutritional Knowledge survey ( p = 0.87), when compared with control group students. Conclusion: Results suggest that the SNACK program was a partial success and is one example of an interdisciplinary approach to early intervention that can teach young children how to choose healthy foods. Abstract : Childhood obesity is a major problem that appears to be on the increase. In this study, researchers evaluated an innovative program integrated into physical education classes for second grade students that aimed to promote healthy eating choices. Findings suggest nutrition education for children as young as seven years old can be useful in teaching them to choose healthy food.